The therapeutic effects of traditional Chinese medicine Fusu agent in LPS-induced acute lung injury model rats - Gao P; Zhao Z; Zhang C; Wang C; Long K; Guo L; Li B (Dove Medical Press, 2018)
Peiyang Gao,1,* Ziyi Zhao,2,* Chuantao Zhang,1 Chunxia Wang,1 Kunlan Long,1 Liuxue Guo,1 Baixue Li31Intensive Care Unit, The Teaching Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, China; 2Central Laboratory, The Teaching Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, China; 3College of Basic Medicine, Chengdu University of Traditional Chinese Medicine, Chengdu, China *These authors contributed equally to this work Purpose: Acute lung injury (ALI) is a common and fatal oxidative stress in the lung, mainly induced by endothelial injury and capillary leakage. In our previous study, “Fusu agent”, a traditional Chinese medicine, was found to exert preventive effect on endothelial damage in lipopolysaccharide (LPS)-induced ALI model rats partially via inhibiting heparanase1 (HPA1) activation and inhibiting the inflammatory factors. However, it is still unknown whether Fusu agent exerts its therapeutic effect in LPS-induced ALI model rats and its potential mechanism.Materials and methods: Rats were injected with LPS (3 mg/kg, intraperitoneally) to induced ALI, and the prepared Fusu agent was given (2, 4 or 6 g/kg) 2 hours after LPS challenge. Twenty-four or 48 hours after Fusu agent administration, the biochemical changes in the plasma and lung tissues and the morphological/histological changes in the lung associated with inflammation and injury were evaluated. Human umbilical vein endothelial cells (HUVECs) were employed to confirm the therapeutic effects of Fusu agent and investigate its mechanisms, that is, affecting ROS accumulation, mitochondrial transmembrane potential (MTP) maintenance and decreasing the expression levels of HPA1.Results: Administration of Fusu agent obviously improved the lung injury and recovered vascular endothelium loss and injury. CD31 signal, which is a specific marker for endothelial vascular lesions, was decreased after Fusu agent treatment in LPS-induced ALI model rats, indicating its therapeutic effect against endothelial surface layer injury. Meanwhile, Fusu agent also decreased HPA1 expression and inflammatory responses. In vitro, Fusu agent-medicated serum decreased injury and cell death induced by LPS in HUVECs by stabilizing MTP and decreasing the leakage of lactate dehydrogenase. Consistently, Fusu agent-medicated serum downregulated HPA1 induced by LPS stimulation.Conclusion: These findings suggest that Fusu agent exerts its therapeutic effect in both LPS-induced ALI model rats and HUVECs potentially via suppressing HPA1 expression, and thus exerts prosurvival effect via maintaining MTP and attenuating cell injury. Keywords: ALI, heparanase, mitochondrial transmembrane potential, HUVECs, acute lung injury, ROS accumulation